SDGs and Human Rights to Food: Integrating Food Security with Climate Change - Sabatira, Febryani; Davey, Orima Melati; Khanza, Yuga Naura; Mirantama, Ninda (Lampung Center for Global Studies (LCGS), 2023)
Food constitutes as the one of a fundamental need of humans and is thus regarded as a form of human rights. The right to food is recognized as a branch of human rights in Article 28H of the 1945 Constitution and the Rome Declaration through the 1996 World Food Summit. Food, as a basic human necessity, has a significant meaning and role in the life of a nation. Inability to sustain food availability to meet demand could cause economic instability. If food security is unbalanced, various social and political upheavals can occur. This critical food situation may jeopardize both economic and national stability. In this regard, Indonesia's efforts to achieve food security are hampered by a variety of crises, including environmental degradation exacerbated by climate change. Because food security is dependent on the production of agricultural products, the quality of the environment plays a significant role, making Indonesia laboriously impacted by climate change. Climate change could severely raise the number of hungers since it embodies an extreme change in weather that disrupts food production stability. Indonesia have been ignoring the real threat of climate change in many aspects including overlooks the risks of food insecurity, which results in non-fulfillment of the human right to food. In this regard, all parties must take the necessary steps to address the issue one way to approach is to implement the Sustainable Development Goals (SDGs).